EXPLORING HOW PERCEPTION MEDIATES THE EFFECT OF HUMOROUS ADVERTISING ON CONSUMER PURCHASE INTENTION, BRAND AWARENESS (Lex localis - Journal of Local Self-Government, 2025)
This study aims to explore how perception influences the effectiveness of humorous advertisements in shaping consumers' purchase intention and enhancing their brand awareness. The study used a survey approach to collect data from a sample of 315 participants, using a questionnaire designed to measure perceptions of humorous advertisements, purchase intention, and consumer brand awareness. The results showed that positive perceptions of humorous advertisements are directly related to increased purchase intention and contribute to enhancing consumer brand awareness. The study also demonstrated that humorous advertisements can create a positive interactive experience with the brand, provided that the advertisement content aligns with the expectations and needs of the target audience. The findings emphasize the importance of combining humor strategies with a comprehensive understanding of consumer perception to achieve effective and sustainable marketing impact, especially in the face of intense competition in modern markets. This study enhances scientific understanding of the role of perception in consumer response to humorous advertisements and provides practical guidance for marketers on designing effective advertising campaigns that enhance purchase intention and increase brand awareness.